The use of narrative text on Students' Reading Comprehension - Dede Rizki Perdiana (Universitas Veteran Bangun Nusantara, 2022)
The goals of the study were derived from the research question describe the effect of using narrative text on students' reading comprehension ability and describe the effectiveness of using narrative text on students' reading comprehension. The This study uses an experimental method with one group pretest and posttest design research instruments. According to (Sugiyono, 2012) the research method is basically a scientific way to obtain data with certain goals and uses. The sample in this study was class VIII SMP NEGERI 5 KOTA SERANG with a total sample of 29 students with a total population of 297, the sampling method in this study was 10% by random sampling. The t-table value for df = 29 is 2.045, as may be inferred from the study and discussion findings. Because the average value of t arithmetic > t table (8.635 > 2.045) from the pretest data is 50.00 and the average value of t arithmetic > t table from the posttest data is 80.00. the learning results using narrative text to improve students' reading comprehension are more effective than using conventional approaches, and these data indicate that there is an increase in students' reading comprehension, supporting the study's premise.